Evaluation Of Strategies For Strengthening Food Security In Sengon Village, Regency As A Disaster-Resilient Village During The Covid-19 Pandemic - Rahmad WIDODO; Bambang PRASTISTHO; Jaka PURWANTA (Journal of Tourism Economics and Policy, 2022)
This study aims to assess Sengon Village's approach to food security during the Covid-19 Pandemic eradication period in Klaten Regency, which has led to significant food security issues in rural areas. When the Covid-19 pandemic first entered Sengon Village and continued to spread rapidly, researchers began working on a strategy to address the issue of food security. They also made attempts to approach the village government about empowering the locals. As a result, many victims in Sengon Village were exposed to Covid-19. Especially in food security, there is still weak supervision, primarily when the Emergency PPKM (Enforcement of Restrictions on Community Activities) is implemented. The research employs Participatory Action Research (PAR) with qualitative supporting data. Evaluation of this strategy is based on the strategies that have been implemented through programs starting from public awareness of food needs, the initial foundation for building food security in the village, to advocacy to the community for the policies of the Sengon village government itself, as well as evaluation of the mapping of sustainable actions. Post-research by analyzing village communities related to food security to food security institutions, one of which is the Women Farmers Group (KWT), to build and encourage an increase in food security in the village. The results of this study indicate that the evaluation of the food security strategy carried out by Destana (Disaster Resilient Village) was carried out very well by Sengon Village as one of the disaster-resilient villages in the Klaten district.